2012
DOI: 10.1136/annrheumdis-2011-201254
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology of gout and hyperuricaemia in Italy during the years 2005–2009: a nationwide population-based study

Abstract: The prevalence of gout and hyperuricaemia increased in Italy from 2005 to 2009. A high recurrence rate for gout attack was observed during the first year following the first episode. Early management of hyperuricaemia in patients at higher risk of recurrent gout attack should be considered in primary care.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

14
145
2
6

Year Published

2015
2015
2016
2016

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 238 publications
(169 citation statements)
references
References 34 publications
(48 reference statements)
14
145
2
6
Order By: Relevance
“…7 It is higher than longitudinal databases of selected populations in the UK (1.4%), US (3.9%) and Italy (0.91%). 10,11,13 The only comparable Australian study is a 2002 Indigenous Australian study 18 , for which self-reported gout was confirmed by clinical examination and investigation, which found an overall prevalence of 3.8% (males 9%, females 0.7%). From a participant self-reported population survey from the Australian Bureau of Statistics (1997Statistics ( -1999, the prevalence of gout was 1.7%.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…7 It is higher than longitudinal databases of selected populations in the UK (1.4%), US (3.9%) and Italy (0.91%). 10,11,13 The only comparable Australian study is a 2002 Indigenous Australian study 18 , for which self-reported gout was confirmed by clinical examination and investigation, which found an overall prevalence of 3.8% (males 9%, females 0.7%). From a participant self-reported population survey from the Australian Bureau of Statistics (1997Statistics ( -1999, the prevalence of gout was 1.7%.…”
Section: Discussionmentioning
confidence: 99%
“…10 Similarly an Italian 2005-2009 primary care database revealed a gout and hyperuricaemia prevalence of only 0.9% and 11.9% respectively. 11 Obesity, hypertension, dyslipidaemia and chronic renal failure have consistently been identified to be increased in the gout population. 8,10,11,12,13 The association of diabetes mellitus and a current smoking history are less well defined with some studies finding them to be less prevalent in people with gout.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the US, the gout prevalence in adults, from patient self-reports of health professional-diagnosed gout in the National Health and Nutrition Examination Survey, increased from 2.7% to 3.9% from the period 1988-1994 to 2007-2008 (2). In Italy, a much lower prevalence was calculated with data from a large national primary care database, which nevertheless significantly increased from 0.67% in the adult population in 2005 to 0.91% in 2009 (3). In another recent study, also involving data from a large sample of general practitioners, gout prevalence in the whole UK population increased by 63.9% between 1997 and 2002, to reach an estimated prevalence of 2.5% (95% confidence interval [95% CI] 2.48-2.51) in 2012, the highest prevalence ever recorded in Europe (4).…”
Section: Introductionmentioning
confidence: 96%
“…This is a rheumatology practice–based multicenter cohort that ensures high reliability in the assessment but selection of more severe or refractory disease. Of note, we included a relatively higher proportion of men than expected in a general population sample 25. Further validation in a primary care setting is worthwhile to define its generalizability.…”
Section: Discussionmentioning
confidence: 99%